2018
DOI: 10.1111/cpf.12518
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of changes in Bone Scan Index at different acquisition time‐points in bone scintigraphy

Abstract: Bone Scan Index (BSI) is a validated imaging biomarker to objectively assess tumour burden in bone in patients with prostate cancer, and can be used to monitor treatment response. It is not known if BSI is significantly altered when images are acquired at a time difference of 1 h. The aim of this study was to investigate if automatic calculation of BSI is affected when images are acquired 1 hour apart, after approximately 3 and 4 h. We prospectively studied patients with prostate cancer who were referred for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Shintawati et al found that both the BSI and number of hotspots tend to increase with an increase in uptake duration (i.e., 2-h, 4-h, or 6-h); therefore, they suggested that the uptake time for each patient should be fixed during follow-up or monitoring [ 18 ]. In addition, Kaboteh et al reported a statistically significant increase in the BSI between uptake times of 1 h, 3 h, and 4 h [ 19 ]. They also suggested that the uptake time should be standardized if patients are repeatedly monitored using bone scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…Shintawati et al found that both the BSI and number of hotspots tend to increase with an increase in uptake duration (i.e., 2-h, 4-h, or 6-h); therefore, they suggested that the uptake time for each patient should be fixed during follow-up or monitoring [ 18 ]. In addition, Kaboteh et al reported a statistically significant increase in the BSI between uptake times of 1 h, 3 h, and 4 h [ 19 ]. They also suggested that the uptake time should be standardized if patients are repeatedly monitored using bone scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…reported a statistically signi cant increase in the BSI between uptake times of 1 h, 3 h, and 4 h. [17] They also suggested that the uptake time should be standardized if patients are repeatedly monitored using bone scintigraphy. Based on our ndings that the mean difference in SUVmax in the parietal bones and jawbone lesion was − 0.04 and 3.8%, respectively, we concluded that the difference in the SUVmax of the 2-and 3-h images was clinically negligible.…”
Section: Discussionmentioning
confidence: 99%
“…A further limitation influencing the performance of the BSI methodology was the kinetics of the tracer. A prolonged time span between administration of the radiopharmaceutical and imaging is known to result in a significantly higher BSI [ 23 , 39 ]. Significant changes in BSI were observed when uptake time was extended from three to four hours post-injection [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prolonged time span between administration of the radiopharmaceutical and imaging is known to result in a significantly higher BSI [ 23 , 39 ]. Significant changes in BSI were observed when uptake time was extended from three to four hours post-injection [ 39 ]. Since all evaluated bone scans were performed in the context of clinical routine, the uptake time was chosen within the limits of the respective guidelines.…”
Section: Discussionmentioning
confidence: 99%